Compliance with Upper Limb Home-Based Exergaming Interventions for Stroke Patients: A Narrative Review - Axelle Gelineau; Anaick Perrochon; Jean-Christophe Daviet; Stephane Mandigout (Medical Journals Sweden, 2022)
Background: Telerehabilitation and follow-up techniques have been developed in recent years to assess the effectiveness of diverse intervention programmes that include exergaming technologies. For patients with upper limb impairment after stroke, motion-gaming technologies can provide effective and amusing training. Beyond efficiency, professionals must analyse patient compliance with the system for self-use at home, because patients may or may not independently perform the exercises prescribed by the therapist. Questions on the sustainable use of this type of home exercise also arise. Objective: This review examines user compliance with exercise programmes, measured according to the training rate (percentage of prescribed sessions and minutes completed) and completion rate (number of drop-outs and discontinued interventions) reported or calculable according to the data collected. Results and discussion: Rates of compliance with training were relatively high. No group effect on compliance was found. Drop-out and discontinued intervention rates were either due to external causes or directly related to the technologies. Some studies have reported the use of supervision, most of them through home visits and remote support. Few studies performed long-term follow-up, which could provide information to help broaden practices. This narrative review considers how this field of research may evolve in the future. LAY ABSTRACT The use of video games in hospitals as a rehabilitation tool in neurology is developing, particularly for stroke victims. For patients with arm problems, it can be effective and fun to use gamified systems. When the patient goes home, they must continue their rehabilitation in order to continue to progress or maintain their skills. However, performing exercises alone at home raises questions about patients' compliance with the exercises prescribed by their therapists. Do patients complete the prescribed sessions? Are there occasional or permanent interruptions? This narrative review attempts to address these questions. The review also examines the obstacles that might hinder the use of these technologies and the facilitators that may help compliance.